Controlling the assembly and spin transport of tetrathiafulvalene carboxylate coated iron oxide nanoparticles. Issue 29 (17th July 2017) - Lv, Zhong-Peng; Wang, Tao; Ge, Jing-Yuan; Luan, Zhong-Zhi; Wu, Di; Zuo, Jing-Lin; Sun, Shouheng
Abstract : The transport mechanism and magnetoresistance of tetrathiafulvalene-carboxylate-coated Fe3 O4 nanoparticle assemblies are finely tuned using controlled ligand engineering, solvent-polarity and NP assembly patterns. Abstract : We report a solution phase based assembly method to tune the transport mechanism and magnetoresistance (MR) of Fe3 O4 nanoparticles (NPs). The NP topological arrangement is altered by the NP coating of tetrathiafulvalene carboxylic acid (TTFCOOH) or its dicarboxylic analogue (TTF(COOH)2 ). Consequently, the transport mechanism of the assembly switches from tunneling to Mott hopping. The MR ratios of the Fe3 O4 NP assemblies can be further tuned by the polarity of the solvent used in the ligand exchange process. The TTF(COO)2 -coated Fe3 O4 NP assembly has a 5% room temperature MR ratio, which is the highest value among all TTF-COO-Fe3 O4 NP assemblies reported so far.